Pengembangan Media Pembelajaran Interaktif Menggunakan Google Sites pada Materi Keanekaragaman Hayati di Kelas XB MA Al Fattahiyyah - Malika, Himatul Askin; Rozi, Fahrur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Development of Interactive Learning Media Using Google Sites on Biodiversity Material in Class XB of MA Alfattahiyyah. Undergraduate Thesis, Study Program of Information Technology Education, Faculty of Science and Technology, Universitas Bhinneka PGRI. Supervisor: Fahrur Rozi, M.Kom. Interactive learning media is one of the innovations in the learning process aimed at increasing student engagement and facilitating understanding of the material. This study aims to develop a Google Sites-based interactive learning media that is feasible to be used for the topic of Biodiversity in class XB of MA Alfattahiyyah. The development process followed the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation.This study developed interactive learning media based on Google Sites for the topic of Biodiversity in class XB of MA Alfattahiyyah using the ADDIE model. Involving media experts, subject matter experts, and students, the validation results showed a very high level of feasibility: 97% from media experts, 96% from subject matter experts, and 89.8% from students. The media was considered highly feasible to be used as an alternative teaching material to enhance students’ motivation and understanding.